Rehabbed to Death: Breaking the Cycle. Issue 11 (28th August 2019) - Flint, Lynn A.; David, Daniel; Lynn, Joanne; Smith, Alexander K.
Abstract : Many older adults transfer from the hospital to a post‐acute care (PAC) facility and back to the hospital in the final phase of life. This phenomenon, which we have dubbed "Rehabbing to death, " is emblematic of how our healthcare system does not meet the needs of older adults and their families. Policy has driven practice in this area including seemingly benign habits such as calling PAC facilities "rehab." We advocate for practice changes: (1) calling PAC "after‐hospital transitional care, " rather than "rehab"; (2) adopting a serious illness communication model when discussing new care needs at the end of a hospitalization; and (3) policies that incentivize comprehensive care planning for older adults across all settings and provide broad support and training for caregivers. In realigning health and social policies to meet the needs of older adults and their caregivers, fewer patients will be rehabbed to death, and more will receive care consistent with their preferences and priorities. J Am Geriatr Soc 67:2398–2401, 2019 Abstract : See related editorial by Ouslander and Grabowski